Direitos Humanos e conservadorismo contemporâneo: a agenda dos deputados do Partido Social Liberal (PSL) 56ª Legislatura (2019-2023) - Barros, Dalila Rodrigues (2024)
In recent years, political events have highlighted the importance of studies on growing conservatism and its ramifications in the institutional sphere. Contrary to the expectations of political scientists, the election of Jair Bolsonaro (PSL/RJ) was not limited to the executive power, but extended to the legislative scope, with a movement that formed around him during the campaign period. As a result, the impact of this politician was to boost the second largest group in the Chamber of Deputies with 53 parliamentarians. However, the strengthening of the conservative reaction is not limited to the 2018 elections, as it manifests itself in other events that marked the strengthening of conservative alliances. One of the effects of this strengthening is the reaction to the launch of the third edition of the National Human Rights Plan (PNDH-3) at the end of 2009, sanctioned by the Lula II government (2006-2010). In this sense, based on the hypothesis that a conservative agenda is underway in the Chamber of Deputies that promotes the regression of rights already achieved by marginalized groups in politics, such as women, black people, indigenous people, and Lesbian, Gay, Bisexual, and Transgender (LGBT) people, our research questions are: what is the conservative agenda of PSL deputies in relation to Human Rights during the 56th Legislature (2019-2023)? And what issues are raised for different vulnerable groups? The methodology adopted in this research was the case study as an investigative modality through statistical techniques with the Iramuteq software. The analysis focused on the selection of 480 bills that correspond to the 56th Legislature presented by the 53 PSL deputies taken from the Chamber of Deputies' own website. These bills were subsequently analyzed from the perspective of the 25 Guidelines of the PNDH-3. Based on the bills presented by the deputies and the analysis of vulnerable groups, such as children and adolescents, women, prisoners and the LGBT population, it is clear that there is a conservative advance that does not limit itself to the current legal and constitutional precepts. Above all, it is a movement that seeks to modify the legal system to meet specific interests and follow an ultra-conservative agenda, often to the detriment of fundamental human rights, making the protection of vulnerable groups more flexible. Another point to highlight from the analyses is the convergence of the public security agenda, which acts as an organizing axis, serving different purposes, depending on the vulnerable group in question.